2011
DOI: 10.1002/ange.201101016
|View full text |Cite
|
Sign up to set email alerts
|

Cyano Groups as Probes of Protein Microenvironments and Dynamics

Abstract: Sondentest: Die Cyangruppe reagiert auf ihre Umgebung, absorbiert in einem einzigartigen Bereich von Protein‐IR‐Spektren und kann an Aminosäuren gebunden werden. Mit stationären und zeitaufgelösten Methoden wurde sie in mehreren Cytochrom‐c‐Varianten (siehe Struktur der Hämtasche) als nützliche ortsspezifische Sonde für Proteinmikroumgebungen und ‐dynamiken belegt; doch sie kann ihre Umgebung auch stören und den gefalteten Proteinzustand destabilisieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…-N 3 [27,[49][50][51], or -C≡N [28,52] groups, many of which have been summarized in recent reviews [53,54]. Of course, with such labels one gives up one of the beauties of IR spectroscopy, i.e., one has to chemically modify the protein, but many of these IR labels are small perturbations in comparison to for example fluorescence labels.…”
Section: Advancing the Selectivitymentioning
confidence: 99%
“…-N 3 [27,[49][50][51], or -C≡N [28,52] groups, many of which have been summarized in recent reviews [53,54]. Of course, with such labels one gives up one of the beauties of IR spectroscopy, i.e., one has to chemically modify the protein, but many of these IR labels are small perturbations in comparison to for example fluorescence labels.…”
Section: Advancing the Selectivitymentioning
confidence: 99%
“…The non‐canonical amino acid (ncAA) 4‐cyano‐L‐phenylalanine (pCNF) is a vibrational reporter which has been incorporated into a number of peptides including the MLCK peptide, the villin headpiece subdomain, the human islet amyloid polypeptide, and the amyloid peptide (A β 16‐22), by standard solid‐phase peptide synthesis. Genetic incorporation through the amber codon suppression method has also been used to incorporate pCNF into several protein systems including myoglobin, the N‐terminal domain of the L9 protein (NTL9), cytochrome c , superfolder green fluorescent protein (sfGFP), the N‐terminal Src homology 3 domain of the murine adaptor protein Crk‐II (nSH3), plastocyanin protein (Pc), and the heme nitric oxide and/or oxygen (H‐NOX) protein from Caldanaerobacter subterraneus ( Cs H‐NOX) . Finally, nitrile vibrational reporters have also been incorporated post‐translationally though the conversion of a cysteine to a thiocyanate (SCN) or by using enzyme inhibitors containing nitriles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the past decade has seen a continued effort to develop extrinsic IR probes that can circumvent this limitation. 1,5 For instance, to improve the structural and spatial resolution of IR measurements, non-natural amino acids consisting of a unique vibrational probe, such as a ACN, ASCN, or AN 3 moiety, have been utilized in various studies, including those concerning protein folding, 6 amyloid formation, 7 the structure and function of membrane proteins, 8,9 electrostatic field of enzymes, [10][11][12][13][14] and drug binding. 15,16 Recently, Pazos et al 17 have shown that the ester carbonyl stretching vibration is a useful and convenient site-specific IR probe of protein electrostatics because (1) its frequency is linearly correlated with the local electrostatic field, even when the carbonyl group is engaged in hydrogen-bonding interactions; (2) its frequency is located in the spectral range of 1700-1800 cm 21 , wherein no intrinsic protein vibrations show up at neutral pH; and (3) it has a relatively high extension coefficient.…”
Section: Introductionmentioning
confidence: 99%